Exploring The Challenges of Communicative Language Teaching in Indonesian Context from a Constructivist Perspective - Izzuddin Hakim (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
A communicative approach has been included in Indonesia's English curriculum since the introduction of the 1984 Curriculum. However, despite its popularity, CLT (Communicative Language Teaching) posited some cultural constraints. These constraints are caused by different views of the learning and teaching process in different cultures. This study explores the challenges of implementing such a teaching approach from a constructivist point of view. The primary aim of this article is to provide insightful information about those challenges which may, then, contribute to a deeper understanding of the issue. The descriptive qualitative approach was used in this study. The study concludes that cultural constraints to the implementation of CLT in the Indonesian context do not necessarily come from cultural aspects. Using a constructivist paradigm, this essay provides an alternative explanation on why students are reluctant to engage in a communicative approach in the Indonesian context: (1) the failure of representation to occur in the teaching instructions and teaching materials during the learning process, and (2) identity-caused reluctance to communicative competence.